Common targetable inflammatory pathways in brain transcriptome of autism spectrum disorders and Tourette syndrome - Alshammery, Sarah; Patel, Shrujna; Jones, Hannah F.; Han, Velda X.; Gloss, Brian S.; Gold, Wendy A.; Dale, Russell C. (Frontiers in Neuroscience, 2022)
Neurodevelopmental disorders (NDDs), including autism-spectrum disorders (ASD) and Tourette syndrome (TS) are common brain conditions which often co-exist, and have no approved treatments targeting disease mechanisms. Accumulating literature implicates the immune system in NDDs, and transcriptomics of post-mortem brain tissue has revealed an inflammatory signal. We interrogated two RNA-sequencing datasets of ASD and TS and identified differentially expressed genes, to explore commonly enriched pathways through GO, KEGG, and Reactome. The DEGs [False Discovery Rate (FDR) <0.05] in the ASD dataset (n = 248) and the TS dataset (n = 156) enriched pathways involving inflammation, cytokines, signal transduction and cell signalling. Of the DEGs from the ASD and TS analyses, 23 were shared, all of which were up-regulated: interaction networks of the common protein-coding genes using STRING revealed 5 central up-regulated hub genes: CCL2, ICAM1, HMOX1, MYC, and SOCS3. Applying KEGG and Reactome analysis to the 23 common genes identified pathways involving the innate immune response such as interleukin and interferon signalling pathways. These findings bring new evidence of shared immune signalling in ASD and TS brain transcriptome, to support the overlapping symptoms that individuals with these complex disorders experience.